Double-Glide Method Using Cathereep Protective Sheet As a Substitute in Descemet's Stripping Automated Endothelial Keratoplasty. (18th September 2013) - Toshida, Hiroshi; Honda, Rio; Matsui, Asaki; Matsuzaki, Yusuke; Shimizu, Yusuke; Seto, Takahiko; Ohta, Toshihiko; Murakami, Akira
Abstract : Purpose . For the insertion of the donor graft in Descemet's stripping automated endothelial keratoplasty (DSAEK), the double-glide method using a Busin glide and intraocular lens (IOL) glide concomitantly has been shown to be effective. The aim of this report is to evaluate the results for the double-glide method using Cathereep (Nichiban, Tokyo, Japan), a protective sheet made of polyurethane film for medical use, as a substitute for an IOL glide. Materials and Methods . The subjects were 10 eyes of 10 patients with bullous keratopathy. The DSAEK operation was performed, and the double-glide method was used for the donor graft insertion. During the operation, an IOL glide was used for the 5 eyes, and the Cathereep protection sheet was used for the remaining 5 eyes. We trimmed approximately 5 mm wide strips from the nonadhesive area surrounding the Cathereep protection sheet. Results . The donor graft was inserted equally easily with the Cathereep protective sheet and IOL glides and improvement of visual acuity was noted in both groups significantly. A favorable postoperative course was obtained with no perioperative complications including endothelial damage. Conclusions . Cathereep protective sheet can be used as a substitute for an IOL glide for double-glide method in DSAEK.